Local emergence in Amazonia of Plasmodium falciparum k13 C580Y mutants associated with in vitro artemisinin resistance - Luana C Mathieu; Horace Cox; Angela M Early; Sachel Mok; Yassamine Lazrek; Jeanne-Celeste Paquet; Maria-Paz Ade; Naomi W Lucchi; Quacy Grant; Venkatachalam Udhayakumar; Jean SF Alexandre; Magalie Demar; et al. (eLife, 2020)
Antimalarial drug resistance has historically arisen through convergent de novo mutations in Plasmodium falciparum parasite populations in Southeast Asia and South America. For the past decade in Southeast Asia, artemisinins, the core component of first-line antimalarial therapies, have experienced delayed parasite clearance associated with several pfk13 mutations, primarily C580Y. We report that mutant pfk13 has emerged independently in Guyana, with genome analysis indicating an evolutionary origin distinct from Southeast Asia. Pfk13 C580Y parasites were observed in 1.6% (14/854) of samples collected in Guyana in 2016–2017. Introducing pfk13 C580Y or R539T mutations by gene editing into local parasites conferred high levels of in vitro artemisinin resistance. In vitro growth competition assays revealed a fitness cost associated with these pfk13 variants, potentially explaining why these resistance alleles have not increased in frequency more quickly in South America. These data place local malaria control efforts at risk in the Guiana Shield.